Not the Consular Year: Perverting Annalistic Time in Sallust - Cowan, Robert (Histos, 2020)
The consular dating formula situates a work of historiography in the annalistic tradition (or alludes to it from outside) and evokes a complex of Republican norms. Time becomes Republican time and is organised according to the reassuring rhythms of the regular elections, tenures, and relinquishments of magistracies. Scholars have shown how Livy and Tacitus manipulate the formula’s associations to dramatise the disruption or obsolescence of these constitutional forms. Throughout his three works, Sallust produces an even wider range of effects by ironic deployment and radical deformation of the formula.